2017
DOI: 10.3390/cryptography1010004
|View full text |Cite
|
Sign up to set email alerts
|

Cryptography in Wireless Multimedia Sensor Networks: A Survey and Research Directions

Abstract: Wireless multimedia sensor networks will play a central role in the Internet of Things world, providing content-rich information for an uncountable number of monitoring and control scenarios. As more applications rely on multimedia data, security concerns gain attention, and new approaches arise to provide security for such networks. However, the usual resource constraints of processing, memory and the energy of multimedia-based sensors have brought different challenges for data encryption, which have driven t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 83 publications
0
20
0
1
Order By: Relevance
“…The authors in the baseline protocol presented in Costa et al claimed that their scheme is secured against various attacks like user anonymity, perfect forward secrecy, and stolen smartcard. However, after a thorough analysis, it has been observed that this protocol has some flaws shown in the cryptanalysis of the baseline protocol in the followin subsection.…”
Section: Cryptanalysis Of Baseline Protocolmentioning
confidence: 99%
“…The authors in the baseline protocol presented in Costa et al claimed that their scheme is secured against various attacks like user anonymity, perfect forward secrecy, and stolen smartcard. However, after a thorough analysis, it has been observed that this protocol has some flaws shown in the cryptanalysis of the baseline protocol in the followin subsection.…”
Section: Cryptanalysis Of Baseline Protocolmentioning
confidence: 99%
“…The paper focuses on security measures that can be applied in image processing despite the limited resources available at the sensor nodes. Furthermore, there are several works which present solutions to combat specific security issues in VSNs [ 33 , 34 , 35 ]. These include, i.e., watermarking of images, aggregation and comparison of multimedia data from different nodes and cryptography to secure the transmission of images.…”
Section: Related Workmentioning
confidence: 99%
“…The threats for traditional wireless sensor networks may also occur in networks with more powerful sensor motes. Even in wireless multimedia sensor networks, an intruder may rapidly drain the energy of nodes [ 30 ]. It has been shown that mobile devices supporting IEEE 802.11 and IEEE 802.15.1 standards are vulnerable to battery exhaustion attacks [ 31 ].…”
Section: Related Workmentioning
confidence: 99%